Pengaruh Good Corporate Governance, Corporate Social Responsibility, dan Profitabilitas terhadap Nilai Perusahaan Pada Perusahaan LQ45 yang Terdaftar di BEI Tahun 2014 - 2015 - Andi Dedi Zulkarnain Putra; Muhammad Ali; Andi Aswan (Magister Management, Hasanuddin University, 2019)
This study purpose to test hypothesis the influence Good Corporate Governance to profitability, the influence Corporate Social Responsibility to profitability, the influence Good Corporate Governance to value of the firm, the influence Corporate Social Responsibility to value of the firm, the influence profitability to value of the firm, the influence Good Corporate Governance to value of the firm through profitability, and the influence Corporate Social Responsibility to value of the firm through profitability. This study sample was by 28 LQ45 Company listed in the Indonesia Stock Exchange in 2014-2016. The sampling used in this study a purposive sampling. Source of data is secondary data, obtained from the financial statements between the period 20142016 in the Indonesia Stock Exchange and the official website of each LQ45 Company. This study used Path Analysis to analysis data with the help of the program Partial Last Square (PLS) to avoid the many assumptions and obtained the results of definite. The results obtained in this study is Good Corporate Governance has no any influence on profitability, Corporate Social Responsibility has no any influence on profitability, Good Corporate Governance has an influence on value of the firm, Corporate Social Responsibility has an influence on value of the firm, profitability has an influence on value of the firm. The profitability can not become moderating variables which make influence between relationship Good Corporate Governance and Corporate Social Responsibility to value of the firm.